Practical applicantions of DSPs in Process Control - Gyeviki, János; Csiszár, Attila (Acta Agraria Kaposváriensis, 2006)
In this paper, a sliding mode control is implemented on the Texas Instruments TMS320LF2407 digital signal processor (DSP) for control a pneumatic positioning system. As an important driving element, the pneumatic cylinder is widely used in industrial applications for many automation purposes thanks to their variety of advantages, such as: simple, clean, low cost, high speed, high power to weight ratio, easy maintenance and inherent compliance. The pneumatic servo-system is a very nonlinear time-variant control system because of the compressibility of air, the friction force between the piston and the cylinder, air mass flow rate through the servo-valve, etc. Because on control difficulties, caused by the high nonlinearity of pneumatic systems, a robust control method must be applied. Sliding mode control was introduced in the late 1970's as a control design approach for the control of robotic manipulators.
Keywords: DSP; Sliding mode control; Pneumatic system; Positioning